Ultrasensitive Detection of Pathogenic Bacteria by Targeting High Copy Signature Genes - Dong, Qiao; Chen, Jingjing; Wei, Qingqing; Liu, Jinling; Shen, Guoshun; Liu, Baoshan; Zhang, Huan; Wang, Yuanzhi; Chen, Zeliang (Frontiers in Veterinary Science, 2022)
Bacterial load in clinical samples is relatively low and difficult to detect. Improvements in assay sensitivity will greatly reduce false negative results and contribute to more accurate diagnoses. In the present study, we present a new strategy to improve the sensitivity of a nucleic acid assay by detecting the presence of a multi-copy gene. Brucella was used as a test case. The genome sequence of Brucella melitensis was screened and several high copy genes were successfully identified. Sequence analysis and qPCR assays of genomic DNA of bacterial cells revealed high copy number genes showed higher sensitivity for detection. Detection of clinical samples with assays targeting the four signature genes confirmed that high copy genes are found at higher concentrations than single copy gene. Analysis of several other pathogenic bacteria successfully identified high copy number genes that could be used as signature genes. Therefore, this strategy of targeting high copy signature genes represents a universal strategy for the ultrasensitive detection of bacteria.